GE11 peptide-conjugated nanoliposomes to enhance the combinational therapeutic efficacy of docetaxel and siRNA in laryngeal cancers - Xu WW (Dove Medical Press, 2017)
Wei-Wei Xu,1,* Da-yu Liu,2,* Ying-chun Cao,1 Xiang-yun Wang1 1Department of Ear-Nose-Throat, Dongying People’s Hospital, Dongying, 2ENT & HN Surgery Department, Qilu Hospital, Shandong University, Jinan, Shandong, China *These authors contributed equally to this work Abstract: In this study, dual therapeutic-loaded GE11 peptide-conjugated liposomes were developed and applied to enhance therapeutic efficacies of standard-of-care regimens for the treatment of laryngeal cancer. The therapeutic strategy used here was a combination treatment with the chemotherapeutic docetaxel (DTX) and siRNA against the ABCG2 gene that regulates multidrug resistance in many tumor types. Liposome-encapsulated DTX/ABCG2–siRNA molecules were targeted to recognize tumor cells of squamous morphology by conjugation to the EGFR-targeting ligand, GE11. Targeted, drug-infused liposomes were nanosized and exhibited controlled release of DTX. Presence of GE11 peptides on liposomal surfaces enhanced the quantities of liposomal constructs taken up by Hep-2 laryngeal cancer cells. GE11 peptide-conjugated liposomes also enhanced cytotoxic effects against Hep-2 laryngeal cancer cells when compared to treatment with free DTX, thereby reducing IC50 values. Additionally, GE11 peptide-conjugated liposomes had significantly increased anti-tumor and apoptotic effects. Treatments with the GDSL nanoparticle formulation inhibited tumor growth in Hep-2 xenograft-bearing nude mouse models when compared to treatments with non-targeted NP constructs. Treatment of the mouse models with GE11 peptide-conjugated liposomes mitigated toxicities observed after treatment with free DTX. Taken together, liposomal encapsulation of DTX and ABCG2–siRNA improved the anti-tumor effects of treatment with free DTX in Hep-2 cell lines, and conjugation of GE11 peptides to liposomal constructs enhanced anti-tumor efficacies and specificities in laryngeal cancer cells. Keywords: laryngeal cancer, docetaxel, ABCG2–siRNA, anti-tumor efficacy, liposomal chemotherapy carriers, GE11 peptide-targeted liposomes